Overexpression of the cohesin-core subunit SMC1A contributes to colorectal cancer development - Sarogni, Patrizia; Palumbo, Orazio; Servadio, Adele; Astigiano, Simonetta; D’Alessio, Barbara; Gatti, Veronica; Cukrov, Dubravka; Baldari, Silvia; Pallotta, Maria Michela; Aretini, Paolo; Dell’Orletta, Felice; Soddu, Silvia; et al. (Journal of experimental & clinical cancer research, 2019)
Cancer cells are characterized by chromosomal instability (CIN) and it is thought that errors in pathways involved in faithful chromosome segregation play a pivotal role in the genesis of CIN. Cohesin forms a large protein ring that binds DNA strands by encircling them. In addition to this central role in chromosome segregation, cohesin is also needed for DNA repair, gene transcription regulation and chromatin architecture. Though mutations in both cohesin and cohesin-regulator genes have been identified in many human cancers, the contribution of cohesin to cancer development is still under debate. Normal mucosa, early adenoma, and carcinoma samples deriving from 16 subjects affected by colorectal cancer (CRC) were analyzed by OncoScan for scoring both chromosome gains and losses (CNVs) and loss of heterozygosity (LOH). Then the expression of SMC1A was analyzed by immunochemistry in 66 subjects affected by CRC. The effects of SMC1A overexpression and mutated SMC1A were analyzed in vivo using immunocompromised mouse models. Finally, we measured global gene expression profiles in induced-tumors by RNA-seq. Here we showed that SMC1A cohesin core gene was present as extra-copies, mutated, and overexpressed in human colorectal carcinomas. We then demonstrated that cohesin overexpression led to the development of aggressive cancers in immunocompromised mice through gene expression dysregulation. Collectively, these results support a role of defective cohesin in the development of human colorectal cancer.